2016
DOI: 10.1002/ejoc.201600244
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Reaction of Arynes with Tertiary Amines and Aldehydes: Formation of 9‐ and 10‐Membered Dibenzo[1,5]oxaza Heterocycles

Abstract: Abstract:The aryne-mediated three-component reaction of arynes, tertiary amines, and aldehydes followed by intramolecular nucleophilic aromatic substitution afforded novel 9-and 10-membered heterocycles. Thus, the reaction of 2-(trimethyl-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…48 Okuma reported that 9-and 10-membered N,O-containing heterocycles could be synthesized from the reaction between arynes and N-phenylmorpholines and N-methylindolines, respectively (Scheme 13). 49 Zwitterion 37 derived from of arynes, benzannulated tertiary amines, and aromatic aldehydes readily underwent intramolecular nucleophilic aromatic substitution to generate ring-expanded N,O-heterocycles 38.…”
Section: Scheme 12 Three-component Coupling Reaction Of Arynes Tertiary Amines and Carbonyl Moietiesmentioning
confidence: 99%
“…48 Okuma reported that 9-and 10-membered N,O-containing heterocycles could be synthesized from the reaction between arynes and N-phenylmorpholines and N-methylindolines, respectively (Scheme 13). 49 Zwitterion 37 derived from of arynes, benzannulated tertiary amines, and aromatic aldehydes readily underwent intramolecular nucleophilic aromatic substitution to generate ring-expanded N,O-heterocycles 38.…”
Section: Scheme 12 Three-component Coupling Reaction Of Arynes Tertiary Amines and Carbonyl Moietiesmentioning
confidence: 99%
“…The reaction with 4-methylbenzyne ( 1b ) proceeded well, affording 5a and 5a′ in a 1.3:1 ratio and 80% yields. While high regioselectivity (10:1) was observed with 6-methylbenzyne ( 1c ), the yield (46%) was lower than that of the reaction with 4-methylbenzyne. , Symmetrical aryne precursors like dimethoxy ( 1d ) and naphthyl ( 1e ) derivatives afforded single products in 86 and 80% yields, respectively. Decreased yield (35%) was obtained with 4-fluorobenzyne ( 1f ), providing 5e and 5e′ in 4.2:1 ratio.…”
mentioning
confidence: 96%
“…First, we investigated various known nucleophiles for the three-component reaction of arynes in the presence of sulfuryl fluoride (Table ). Several nucleophiles like isocyanides, amines, imines, N -heterocycles, and phosphines have previously been used for MCRs with arynes. We screened various nucleophiles using 2-(trimethylsilyl)­phenyl triflate ( 1a ) as a model substrate, following the procedure reported for each nucleophile.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of our interest in developing transition-metal-free MCCs involving arynes, , we have recently reported the aryne MCCs triggered by aromatic tertiary amines using aldehydes/activated ketones as the third component (Scheme , eq 1). , The reaction afforded ortho -functionalized tertiary amines proceeding via the aryl to aryl amino group migration similar to the Smiles rearrangement . Inspired by this finding, we envisaged the use of CO 2 in aryne MCCs triggered by aromatic tertiary amines.…”
mentioning
confidence: 99%